Antimicrobial susceptibility of Gram-negative and Gram-positive bacteria collected from Eastern Europe: Results from the Tigecycline Evaluation and Surveillance Trial (T.E.S.T.), 2011-2016 - Dowzicky, Michael J; Chmelařová, Eva (Journal of global antimicrobial resistance (Print), 2019)
OBJECTIVES: The Tigecycline Evaluation and Surveillance Trial (T.E.S.T.) is a global surveillance programme monitoring the in vitro activity of a panel of antimicrobial agents against clinically important bacterial isolates. Data for Gram-positive and Gram-negative isolates collected in Eastern Europe between 2011 and 2016 are presented here. METHODS: Minimum inhibitory concentrations (MICs) were determined by the broth microdilution method using CLSI guidelines. Antimicrobial susceptibility was assessed using EUCAST breakpoints. RESULTS: Nine Eastern European countries submitted 4289 isolates. Among Acinetobacter baumannii, resistance to levofloxacin, amikacin and meropenem was 77.5%, 63.4% and 62.2%, respectively. Multidrug resistance among A. baumannii was higher in 2015 than in previous years (44.1% in 2011 and 71.0% in 2015), decreasing to 51.7% in 2016. The multidrug resistance percentage for Pseudomonas aeruginosa was 26.9% and was relatively stable over time. The percentage of extended-spectrum β-lactamase (ESBL)-positive isolates among Escherichia coli and Klebsiella pneumoniae was 20.1% and 55.7%, respectively. Resistance to amikacin, meropenem and tigecycline was low among E. coli and K. pneumoniae and the ESBL-producing subset (≤5.9%). Among Staphylococcus aureus isolates, 36.7% were methicillin-resistant (MRSA); percentages varied year-on-year. No S. aureus isolates, including MRSA, were resistant to linezolid, vancomycin or tigecycline. Among Enterococcus faecium isolates, resistance was 22.6% to vancomycin and 2.3% to linezolid; no isolates were resistant to tigecycline. CONCLUSION: This study shows low resistance to meropenem and tigecycline among Enterobacteriaceae isolates and continued activity of linezolid, vancomycin and tigecycline against Gram-positive organisms. However, antimicrobial resistance continues to be problematic in Eastern Europe and requires continued surveillance.
Keywords: Gram-Negative Bacterial Infections; Microbial Sensitivity Tests; Europe, Eastern; Humans; východní Evropa; lidé středního věku; Female; Aged; mladý dospělý; dospělí; Gram-Positive Bacterial Infections; mikrobiální testy citlivosti; senioři; lidé; Tigecycline; antibakteriální látky; tigecyklin; grampozitivní bakteriální infekce; Adult; ženské pohlaví; Anti-Bacterial Agents; Male; Middle Aged; Drug Resistance, Bacterial; Adolescent; Gram-Negative Bacteria; Young Adult; grampozitivní bakterie; bakteriální léková rezistence; gramnegativní bakteriální infekce; Gram-Positive Bacteria; mužské pohlaví; gramnegativní bakterie; mladiství